Hablemos de Ingles sin miedo (2022)
Acerca del autor Presentación Justificación Objetivo General Objetivo Especifico English Level 1 Interchange Intro Book Unit 1: “It´s Nice to Meet You” Story 1 “Introducing People” Role Play “Getting to Know People” Story 2 “First day of class” Interchange Intro Book Unit 1 “It´s Nice to Meet You” Conversation Interchange Intro Book Unit 2 “What´s this?” Role Play “Wendy´s Birthday” Story 1 “Kate Can´t Find Her Car Keys” Interchange Intro Book Unit 2 “What´s This? Conversation Interchange Intro Book Unit 3 “Where Are You From?” Role Play Story 1 “Looking at Photos” Interchange Intro Book Unit 3 “Where Are You From?” Conversation Interchange Intro Book Unit 4 “Whose Jeans Are These?” Role Play “I´M Wearing…”. Story 2 “It´s Really Cold” Interchange Intro Book Unit 4 “Whose Jeans Are These?” Conversation. Interchange Intro Book Unit 5 “What Are You Doing?”. Story 1 “Chatting At 4:00 A.M” Interchange Intro Book Unit 5 “What Are You Conversation Interchange Intro Book Unit 6 “My Sister Works Downtown” Story 1 “Talking About Schedules” Interchange Intro Book Unit 6 “My Sister Works Downtown” Conversation. Interchange Intro Book Unit 7 “Does It Have a View?” Interchange Intro Book Unit 7 “Does it have a view?” Conversation. Interchange Intro Book Unit 8 “What Do You Do?” Interchange Intro Book Unit 8 “What Do You Do?” Conversation. English Level 2. Interchange Intro Book Unit 9 “Do We Need Any Eggs?” Story1 “Planning A Picnic” Interchange Intro Book Unit 9 “Do We Need Any Eggs?” Conversation. Interchange Intro Book Unit 10 “What Sports Do You Play?” Role Play “I Love Sports” p.64. Interchange Intro Book Unit 10 “What Sports Do You Play?” Conversation. Interchange Intro Book Unit 11 “What Are You Going to Do?” Story 1 “Holidays.” Interchange Intro Book Unit 11 “What Are You Going to Do?” Conversation. Interchange Intro Book Unit 12 “Miss West Goes to The Medical Doctor.” Story 1 “Miss West is feeling awful” Interchange Intro Book Unit 12 “Miss West Goes to The Medical Doctor.” Conversation. Interchange Intro Book Unit 13 “Giving Directions” Role Play. Story 1 “The Tour Guide” Interchange Intro Book Unit 13 “Giving Directions” Conversation. Interchange Intro Book Unit 14 “What I Did On The Last Weekend” Story 1 “My Last Weekend.” Interchange Intro Book Unit 14 “What I Did On The Last Weekend” Conversation. Interchange Intro Book Unit 15 “Where Did You Grow Up?” Story 1 “Turning Pain to Gain” Interchange Intro Book Unit 15 “Where Did You Grow Up?” Conversation. Interchange Intro Book Unit 16 “Can She Call You Later?” Interchange intro book Unit 16 “Can She Call You Later?” . Conversation. English Level 3 Interchange Book 1 Unit 1 “Please Call Me Beth” Role Play:” Where are you from?” Interchange Book 1 Unit 1 “Please Call Me Beth” Conversation. Interchange Book 1 Unit 2 “What Do You Do?” Oral Report: “Why do they need a job?” Interchange Book 1 Unit 2 “What Do You Do?” Conversation. Interchange Book 1 Role Play: “How much is it?” Interchange Book 1 Unit 3 “How Much Is It?” Conversation. Interchange Book 1 Unit 4 “I Really Like Hip Hop”. Oral Report: Biography: “Fergie: Of the Black-Eyed Peas.” Interchange Book 1 Unit 4 “I Really Like Hip Hop” Conversation. Interchange Book 1 Unit 5 “I Come from A Big Family” Oral Report: “Stay-at-home dads.” Interchange Book 1 Unit 5 “I Come from A Big Family” Conversation. Interchange Book 1 Unit 6 “How Often Do You Exercise?” Oral report: “How often do you practice…?” Interchange Book 1 Unit 6 “How Often Do You Exercise?” Conversation. Interchange Book 1 Unit 7 “We Had a Great Time” Oral report: “How was your vacation?” Interchange Book 1 Unit 7 “We Had a Great Time” Conversation. Interchange Book 1 Unit 8 “What´s Your Neighborhood Like?” Interchange Book 1 Unit 8 “What´s Your Neighborhood Like?” Conversation: English Level IV Interchange Book 1 Unit 9 “What Does She Look Like?” Interchange Book 1 Unit 9 “What Does She Look Like? Conversation. Interchange Book 1 Unit 10 “Have You Ever Ridden a Camel”? Story 1. “My Past Experiences ” Interchange Book 1 Unit 10“Have You Hever Ridden A Camel?” Conversation. Interchange Book 1 Unit 11 “It´s A Very Exciting Plac Story 2. “I´ve Been to Cartagena” Interchange Book 1 Unit 11 “It´s A Very Exciting Place” Conversation